The Case of Summerfield - Rhodes, W. H. (William Henry), 1822-1876 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Case of Summerfield" by W. H. Rhodes is a novel that falls within the realm of crime fiction and speculative literature, likely written during the late 19th century. The story revolves around a mysterious and dangerous secret related to water's combustible properties, suggested through the character of Gregory Summerfield, who believes he has discovered a method to ignite water. The narrative delves into themes of morality, fear, and the untamed powers of nature, set against an intriguing historical backdrop. The plot centers on Leonidas Parker, a lawyer, who recounts his association with the enigmatic Summerfield and the chain of events that leads to a tragic death connected to their interactions. As Parker learns of Summerfield's dangerous discovery involving potassium and water, a debate ensues about the implications of holding such a powerful secret. Tensions rise as Parker navigates his moral dilemmas while attempting to manage Summerfield's demands for exorbitant payment in exchange for the formula. Ultimately, the narrative culminates in an act of desperation, intertwining fate, fear for humanity's survival, and the consequences of wielding knowledge that could potentially lead to disaster. (This is an automatically generated summary.)
Release date is 2004-02-01
Produced by David A. Schwan, and David Widger
Keywords: Science fiction